-5c=75

Move the negative in front of the fraction.

-5c=75

Multiply each term by c and simplify.

Multiply each term in -5c=75 by c.

-5c⋅c=75⋅c

Cancel the common factor of c.

Move the leading negative in -5c into the numerator.

-5c⋅c=75⋅c

Cancel the common factor.

-5c⋅c=75⋅c

Rewrite the expression.

-5=75⋅c

-5=75c

-5=75c

Rewrite the equation as 75c=-5.

75c=-5

Divide each term by 75 and simplify.

Divide each term in 75c=-5 by 75.

75c75=-575

Cancel the common factor of 75.

Cancel the common factor.

75c75=-575

Divide c by 1.

c=-575

c=-575

Simplify -575.

Cancel the common factor of -5 and 75.

Factor 5 out of -5.

c=5(-1)75

Cancel the common factors.

Factor 5 out of 75.

c=5⋅-15⋅15

Cancel the common factor.

c=5⋅-15⋅15

Rewrite the expression.

c=-115

c=-115

c=-115

Move the negative in front of the fraction.

c=-115

c=-115

c=-115

c=-115

The result can be shown in multiple forms.

Exact Form:

c=-115

Decimal Form:

c=-0.06‾

Solve for c -5/c=75